De l’augustinisme à la théosophie - Jean-François Alizon (Recherches Germaniques)
Despite the fact that its title definitely suggests an alchemical treatise, the present work by Johann Valentin Andreae proves, when read attentively, to be inspired by biblical theology. As a matter of fact, it is deeply influenced by the theses of Luther and Calvin and, through them, by St. Augustine. Underlying the entire text, the anguish of the main character is perceivable: Have I been the subject of election by divine grace, or not? In 1616, almost a hundred years after the first proclamation of the Reformation, Protestantism was seen by some as having lost some of the spiritual momentum of its founders. In order to breathe new life into it, J.V. Andreae tried to restore the strict approach of Luther, for whom Christian faith was an experience, lived out at a deep inner level. But, as is well-known, Luther was in turn profoundly influenced by St. Augustine’s dualism and the struggle between inner and outer man, spirit and body, the divine and earthly realms. In this context, why did the Chymical Wedding’s author feel the need to use the images and the language of alchemy? In this respect, there appears to be a dual contradiction: at first, in the novel, Andreae seems to poke fun at Paracelsus and at alchemical literature. On the other hand, Lutheran theology is in contradiction with alchemical thought, which seeks to unite spirit and matter, good and evil, male and female. We put forward the following hypothesis: Andreae deeply needed to overcome St. Augustine’s dualism, so to that end he made use of alchemical thought, which was firmly rooted in contemporary culture. Furthermore, it allowed him to conjure up the world of images, which had been rejected by Protestantism. During this era of the Counter Reformation and of the emergence of the Baroque period, he brought back to life the imagination and the world of the soul, in an attempt to restore the living link between spirit and body. By reintegrating the world of the soul and of nature in Protestantism, the Chymical Wedding lays the foundations for the spiritual rebirth of Protestantism, and for the Lutheran theosophy of the late 16th and 17th century, i.e. Weigel, Nicolaï, and Böhme.